Pengaruh Keterampilan Deteksi Dini dan Manajemen Awal Kegawatdaruratan Perdarahan Terhadap Pengetahuan Ibu Hamil di UPTD Puskesmas Way Panji Kabupaten Lampung Selatan - Indah Wahyuningsih; Rilyani Rilyani; Lina Novikasari (Universitas Malahayati Lampung, 2025)
ABSTRACT The World Health Organization (WHO) stated that maternal deaths in 2020 were around 287,000 women who died during and after pregnancy and childbirth. Sub-Saharan Africa 70% of maternal deaths (202,000), South Asia 16% of maternal deaths (47,000). Indonesia's maternal mortality rate is above 15 deaths per 1000 live births. In Lampung Province, the maternal mortality rate in 2023 was 75.15%. South Lampung in 2022 was 29.43%. Early detection of emergencies and provision of appropriate treatment can prevent complications and can result in maternal death. To determine the effect of early detection skills and early management of bleeding emergencies on the knowledge of pregnant women at the Way Panji Health Center, South Lampung Regency in 2024. This study used a quasi-experimental design with one group pre-test - post-test, the population was all pregnant women in the scope of work of the Way Panji Health Center, South Lampung Regency, totaling 326 respondents, the sampling technique used was Purposive Random Sampling with a sample of 30 respondents. The instrument used a questionnaire and the statistical test used was the t-test. The average pre-test knowledge score was 6.33 and the average post-test knowledge score was 13.03. The average pre-test skill score was 4.90 and the average post-test knowledge score was 11.17. The results of the t-test knowledge test (0.000) and skills (0.000) of pregnant women. There is an influence of early detection skills and early management of bleeding emergencies on the knowledge and skills of pregnant women at the Way Panji Health Center, South Lampung Regency in 2024. Keywords: Pregnant Women, Early Detection, Pregnant Women's Emergencies, Knowledge ABSTRAK World Health Organization (WHO) menyatakan kematian ibu hamil tahun 2020 sekitar 287.000 perempuan meninggal selama dan setelah kehamilan dan persalinan. Afrika Sub-Sahara 70% kematian ibu (202.000), Asia Selatan 16 % kematian ibu (47.000). Indonesia angka kematian ibu di atas 15 kematian per 1000 kelahiran hidup. Di Provinsi Lampung angka kematian ibu pada tahun 2023 sebanyak 75,15 %. Lampung Selatan tahun 2022 sebanyak 29,43%. Deteksi dini kegawatdaruratan dan pemberian penanganan yang sesuai dapat mencegah komplikasi dan dapat mengakibatkan kematian ibu. Diketahui Pengaruh Keterampilan Deteksi Dini Dan Manajemen Awal Kegawatdaruratan Perdarahan Terhadap Pengetahuan Ibu Hamil Di Puskesmas Way Panji Kabupaten Lampung Selatan Tahun 2024. Penelitian ini menggunakan diesain desain quasi eksperimen one group Pre-test – Post-test, populasi adalah seluruh ibu hamil yang berada di ruang lingkup kerja Puskemas Way Panji Kabupaten Lampung Selatan yang berjumlah 326 responden, teknik sampling yang digunakan adalah Purposive Random Sampling dengan sampel sebanyak 30 responden. Instrumen menggunakan kuesioner dan uji statistic yang digunakan uji t test. Rata-rata nilai pengetahuan pre test sebesar 6,33 dan rata-rata nilai pengetahuan post test sebesar 13,03. Rata-rata nilai keterampilan pre test sebesar 4,90 dan rata-rata nilai pengetahuan post test sebesar 11,17. Hasil uji t test pengetahuan (0,000) dan keterampilan (0,000) ibu hamil. Ada pengaruh keterampilan deteksi dini dan manajemen awal kegawatdaruratan perdarahan terhadap pengetahuan dan keterampilan ibu hamil di Puskesmas Way Panji Kabupaten Lampung Selatan tahun 2024. Kata Kunci: Ibu Hamil, Deteksi Dini, Kegawatdaruratan Ibu Hamil, Pengetahuan